Extreme magneto-transport of bulk carbon nanotubes in sorted electronic concentrations and aligned high performance fiber - Bulmer, John S.; Lekawa-Raus, Agnieszka; Rickel, Dwight G.; Balakirev, Fedor F.; Koziol, Krzysztof K. (Nature Publishing Group, 2017)
We explored high-field (60T) magneto-resistance (MR) with two carbon nanotube (CNT) material classes: (1) unaligned single-wall CNTs (SWCNT) films with controlled metallic SWCNT concentrations and doping degree and (2) CNT fiber with aligned, long-length microstructure. All unaligned SWCNT films showed localized hopping transport where high-field MR saturation definitively supports spin polarization instead of a more prevalent wave function shrinking mechanism. Nitric acid exposure induced an insulator to metal transition and reduced the positive MR component. Aligned CNT fiber, already on the metal side of the insulator to metal transition, had positive MR without saturation and was assigned to classical MR involving electronic mobility. Subtracting high-field fits from the aligned fiber's MR yielded an unconfounded negative MR, which was assigned to weak localization. It is concluded that fluctuation induced tunnelling, an extrinsic transport model accounting for most of the aligned fiber's room temperature resistance, appears to lack MR field dependence.